Potret Kekerasan Ibu terhadap Anak Perempuan dalam Novel Ibuku Tak Menyimpan Surga di Telapak Kakinya karya Triani Retno A - Sahara, Nurfadilla; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
Research on maternal violence against children in the family is a unique topic. This research aims to discuss the forms of violence, the causes of violence, and the impact of violence in the novel Ibuku Tak Menyimpan Surga di Telapak Kakinya by Triani Retno A. This research is a literary research using qualitative methods. The data collection techniques used in this research are reading and understanding novel Ibuku Tak Menyimpan Surga di Telapak Kakinya by Triani Retno A, conducting literature studies, marking and recording data, and inventorying data. The technique of analyzing data in this study is classifying data, analyzing data in accordance with the theory of Sociology of Literature, drawing conclusions based on research findings. The results show that the forms of violence in the novel are physical violence, psychological violence, sexual violence, and economic violence. The causes of violence found are divided into internal factors and external factors. Third, the impacts of violence include mental health, behavior, physical health, economic, and social. Violence that appears in popular novels is a portrait of reality that shows the same social symptoms.